Does the circulating ketoconazole metabolite N-deacetyl ketoconazole contribute to the drug-drug interaction potential of the parent compound? - Weiß, Johanna; Foerster, Kathrin; Weber, Maria; Burhenne, Jürgen; Mikus, Gerd; Lehr, Thorsten; Haefeli, Walter E. (European journal of pharmaceutical sciences, 2022)
Ketoconazole is a strong inhibitor of cytochrome P450 3A4 (CYP3A4) and of P-glycoprotein (P-gp) and is often used as an index inhibitor especially for CYP3A4-mediated drug metabolism. A preliminary physiologically based pharmacokinetic (PBPK) model for drug-drug interactions indicated possible involvement of a metabolite to the perpetrator potential of ketoconazole. Still unknown for humans, in rodents, N-deacetyl ketoconazole (DAK) has been identified as the major ketoconazole metabolite. We therefore investigated in vitro, whether DAK also inhibits the human CYPs and drug transporters targeted by ketoconazole and quantified DAK in human plasma from healthy volunteers after receiving a single oral dose of 400 mg ketoconazole. Our data demonstrated that DAK also inhibits CYP3A4 (2.4-fold less potent than ketoconazole), CYP2D6 (13-fold more potent than ketoconazole), CYP2C19 (equally potent), P-gp (3.4-fold less potent than ketoconazole), breast cancer resistance protein (more potent than ketoconazole) and organic anion transporting polypeptide 1B1 and 1B3 (7.8-fold and 2.6-fold less potent than ketoconazole). After a single oral dose of 400 mg ketoconazole, maximum concentrations of DAK in human plasma were only 3.1 ‰ of the parent compound. However, assuming that DAK also highly accumulates in the human liver as demonstrated for rodents, inhibition of the proteins investigated could also be conceivable in vivo. In conclusion, DAK inhibits several CYPs and drug transporters, which might contribute to the perpetrator potential of ketoconazole.